Handbook of Sustainable Luxury Textiles and Fashion Volume 2 - Gardetti, Miguel Angel; Muthu, Subramanian Senthilkannan (Environmental Footprints and Eco-design of Products and Processes,, 2016)
The second volume of handbook explores different dimensions of the sustainable luxury textiles and fashion, broadly based on the following topics:  Sustainable luxury Luxury and consumption Luxury, innovation and design potential Luxury and entrepreneurship Sustainable Luxury Management.